Uji Penggunaan Beberapa Jenis Kompos Pada Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Main Nursery - Stevanus, Jan Buha; Sri Yoseva, Sri; ', Sampoerno (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The development of oil palm cultivation relating to the availability of quality seeds, one way getting quality seeds is by the addition of nutrients through fertilization using compost. This research aimed to determine the effect of the type of compost and the best compost for the growth of main nursery oil palm seedlings. This research was conducted at the land of the Plants Laboratory in Agriculture Faculty, University of Riau for 4 months. This research was carried out experimentally using completely randomized design (CRD) consisting of 6 utilizing several types of compost are: K1 = oil palm empty fruit bunches compost, K2 = male flowers of oil palm compost, K3 = rice straw compost, K4 = compost LCC, K5 = compost vegetable waste and K6 = municipal solid waste compost, with 4 replications. The data were statistically analyzed using analysis of variance and further tested using Duncan's New Multiple Range Test (DNMRT) at the level of 5%. The results showed that the utilizing of several types of compost (100 g/10 kg soil) had no significant effect on seedling height accretion, number of leaves, leaf length, dry weight of plant, crown root ratio and seed quality indices, but had significant effect on girth hump accretion. utilizing of male flowers of oil palm compost (100 g/10 kg soil) provide girth hump accretion, dry weight of plant and seed quality indices tend to be higher than other compost. Keywords : Oil palm, several types of compost